2020
DOI: 10.1038/s41559-020-1111-z
|View full text |Cite
|
Sign up to set email alerts
|

Complex long-term biodiversity change among invertebrates, bryophytes and lichens

Abstract: Large-scale biodiversity change is measured largely through the responses of a few taxonomic groups. Much less is known about the trends affecting most invertebrates and other neglected taxa, and it is unclear whether well-studied taxa, such as vertebrates, reflect changes in wider biodiversity. Here, we present and analyse trends in the UK distributions of over 5,000 species of invertebrates, bryophytes and lichens, measured as changes in occupancy. Our results reveal substantial variation in both the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(197 citation statements)
references
References 57 publications
10
187
0
Order By: Relevance
“…S3) are the ones showing the clearest 225 signal for decline (Fig. S4); our results agree with several existing reports at local, national 226 and subcontinental level 14,16,17,39,[56][57][58][59][60][61] . Furthermore, none of those biases can explain the noticeable phylogenetic contagion seen in the trends (Fig.…”
Section: Zattara and Aizen -9supporting
confidence: 91%
“…S3) are the ones showing the clearest 225 signal for decline (Fig. S4); our results agree with several existing reports at local, national 226 and subcontinental level 14,16,17,39,[56][57][58][59][60][61] . Furthermore, none of those biases can explain the noticeable phylogenetic contagion seen in the trends (Fig.…”
Section: Zattara and Aizen -9supporting
confidence: 91%
“…Many studies on biodiversity change have focused on the simple long-term mean trend of a species but this approach can mask a diversity of more complex temporal responses (Outhwaite et al 2020). Indeed, recent analyses of invertebrate changes in the UK found both time-periods of increases and time-periods of decreases, which varied among taxa (Macgregor et al 2019;Outhwaite et al 2020). For instance, UK freshwater organisms decreased between 1970 and the mid-1990s but increased from then until 2010 (Outhwaite et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent analyses of invertebrate changes in the UK found both time-periods of increases and time-periods of decreases, which varied among taxa (Macgregor et al 2019;Outhwaite et al 2020). For instance, UK freshwater organisms decreased between 1970 and the mid-1990s but increased from then until 2010 (Outhwaite et al 2020). Moreover, simple trend models can produce trend estimates driven by fluctuations in particular years (Seibold et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of long-term phenological and population data is valuable in understanding the effects of climate change on species assemblages (Renner & Zohner, 2018). For insects, such data are often only available for high-profile taxa (Saunders et al, 2020), and it has been shown that these are not always representative of other taxonomic groups (Bell et al, 2020;Outhwaite et al, 2020). Insects form a vital component of most terrestrial and freshwater ecosystems (Hershey et al, 2010;Mooney et al, 2010;Vidal & Murphy, 2019).…”
Section: Introductionmentioning
confidence: 99%